Evolutionary History of Plant LysM Receptor Proteins Related to Root Endosymbiosis - Gough, Clare; Cottret, Ludovic; Lefebvre, Benoit; Bono, Jean-Jacques (Frontiers in Plant Science, 2018)
LysM-Receptor-Like Kinases (LysM-RLKs), which are specific to plants, can control establishment of both the arbuscular mycorrhizal (AM) and the Rhizobium-legume (RL) symbioses in response to signal molecules produced, respectively, by the fungal and bacterial symbiotic partners. While most studies on these proteins have been performed in legume species, there are also important findings that demonstrate the roles of LysM-RLKs in controlling symbiosis in non-legume plants. Phylogenomic studies, which have revealed the presence or absence of certain LysM-RLKs among different plant species, have provided insight into the evolutionary mechanisms underlying both the acquisition and the loss of symbiotic properties. The role of a key nodulation LysM-RLK, NFP/NFR5, in legume plants has thus probably been co-opted from an ancestral role in the AM symbiosis, and has been lost in most plant species that have lost the ability to establish the AM or the RL symbiosis. Another LysM-RLK, LYK3/NFR1, that controls the RL symbiosis probably became neo-functionalised following two rounds of gene duplication. Evidence suggests that a third LysM-RLK, LYR3/LYS12, is also implicated in perceiving microbial symbiotic signals, and this protein could have roles in symbiosis and/or plant immunity in different plant species. By focusing on these three LysM-RLKs that are widespread in plants we review their evolutionary history and what this can tell us about the evolution of both the RL and the AM symbioses.